Unravelling the Sequence and Timing of Fault-Related Deformation in Superimposed Rift Basins, Inner Moray Firth, NE Scotland - Alexandra Tamas; Robert E. Holdsworth; Dan M. Tamas; Edward D. Dempsey; Kit Hardman; Anna Bird; John R. Underhill; Dave McCarthy; Ken J. W. McCaffrey; David Selby (Lithosphere)
Devonian rocks of the Palaeozoic Orcadian Basin are well exposed along the northern flanks of the younger Mesozoic to Cenozoic Inner Moray Firth Basin in Scotland. These rocks preserve a succession of structures related to superimposed rifting and inversion events spanning nearly 400 Myrs. We combine new detailed field observations augmented by drone photography and the creation of 3D digital outcrops, coupled with U-Pb geochronology of syn-faulting calcite-mineralized veins to better constrain the absolute timing of fault movements and decipher the kinematic history of basin opening and inversion.Using this approach, we were able to isolate characteristic structures, fault kinematics, fault rock development and associated mineralization types related to five regional deformation events: (1) Devonian transtensional rifting associated to sinistral Great Glan Fault movements leading to the development of the Orcadian Basin; (2) Late Carboniferous inversion related to dextral Great Glen Fault reactivation; (3) minor N-S, possibly Permian calcite veins; (4) Late Jurassic–Early Cretaceous rifting related to the development of the IMFB; and finally, (5) Cenozoic uplift, reactivation, and local inversion. Our study demonstrates the utility of microstructurally constrained U-Pb geochronology of fault-related calcite mineralization. Applied elsewhere, our methodology has the potential to give consistent and regionally significant new insights into the nature and timing of superimposed rift-related deformation processes worldwide.